Big data technology and near real-time production tracking to improve small-scale fisheries management - CGIAR Platform for Big Data in Agriculture (2019)
National level uptake of the innovation by the government of Timor-Leste in May 2019 as their official fisheries monitoring system. 359 solar-powered tracking devices were installed on fishing boats in Timor-Leste." plan to install 500 in 2020.